The Protection of Constitutional Identity in Some East-Central European Countries - Nagy Gellért (Opolskie Studia Administracyjno-Prawne)
Constitutional identity is, in its essence, an expression of the fundamental constitutional values of a state. The protection of all these values is of paramount importance, both in domestic law and in the relationship between eU law and national constitutions. While the former can be linked with the concept of unconstitutional amendments to the Constitution, the latter has resulted in the development of identity control. This contribution aims to examine these two aspects of constitutional identity in the case of seven east-Central european countries (romania, the Czech republic, Croatia, Slovakia, Poland, and Hungary). although what constitutes part of a state’s constitutional identity varies from nation to nation, one can notice that certain values, such as the protection of fundamental human rights and freedoms are broadly embedded. This contribution seeks to focus on all these similarities and differences through a comparison of the constitutional identities of the states under examination.